THE RAMIFICATIONS OF CLIMATE VARIABILITY IN AGRICULTURAL FOOD CROPS PRODUCTION AMONG THE SMALLHOLDER FARMERS IN SOUTHERN HIGHLANDS, TANZANIA - GWAMBENE, BROWN (Journal of Ecobiotechnology, 2018)
Implication of climate variability and changing environment potentially subvert agricultural crop production of subsistence and smallholder farmers in the developing countries. Ensuring food security during increasing environmental changes and climate variability constitutes one of the greatest adaptation challenges. Understanding the complex nature of food security and emphasis on increasing food crop production and distribution provide substantial adaptation option and an opportunity for spearheading, generating of information, developing of innovative and improving technologies to adapt to anticipated situations. This paper employed survey to collect information. The study results ascribe that the heavy reliance on rain-fed agriculture, shortage of land and the use of poor technology renders many smallholder farmers vulnerable to the effects of climate variability resulting in the decline of agricultural production, hence food insecurity. The trend is likely to worsen if no measures are put in place to redress the situation. In addressing such challenges, substantial efforts are needed to improve farming practices and the development of adaptation measures that include diversification, climate smart farming practices and improvement of extension and veterinary services. For effectiveness of adoption this will need to include promotion of appropriate and inclusive, environmentally-sound technologies and an enabling policy environment that reinforces actions at the all levels.